Between the Aesthetics of Picturesque and the Documentary Uses: The Images of Popular Types and Customs in Chile and Peru’S 19th Century Visual Culture [Entre Lo Pintoresco y Lo Documental: Los Tipos Populares en la Cultura Visual de Chile y Perú Durante el Siglo Xix] - Delpiano-Kaempffer, M (Universidad de los Lagos, 2021)
Images of popular types and customs were set up as fundamental repertoires in the structure of nation imaginaries in Latin America, hence the importance of its study in order to understand nineteenth-century visual culture in territories such as Chile and Peru. These representations were mainly developed from manual media, in which are discussed matters of taste, associated to an aesthetic of the picturesque; this shows the tensions and convergences of various functions and demands of the model image. However, during the second half of the nineteenth century, this tradition will confront the emergence of the photographic medium. The repercussions and transformations which this implied will be discuss in the present article, considering both the documentary and the informative component that photography would have boost into a repertoire which was mostly constituted, though not exclusively, by an aesthetic of the picturesque. In this way, this paper proposes a historiographic reading that analyses the setting-up of this tradition through particular cases refer to the Chilean and Peruvian context, to think afterwards its reformulation following the incursion of the technical device. © 2021, Universidad de los Lagos. All rights reserved.